Lymph node fibroblastic reticular cells preserve a tolerogenic niche in allograft transplantation through laminin α4 - Lushen Li; Marina W. Shirkey; Tianshu Zhang; Wenji Piao; Xiaofei Li; Jing Zhao; Zhongcheng Mei; Yizhan Guo; Vikas Saxena; Allison Kensiski; Samuel J. Gavzy; Yang Song; et al. (The Journal of Clinical Investigation, 2022)
Lymph node (LN) fibroblastic reticular cells (FRCs) define LN niches and regulate lymphocyte homeostasis through producing diverse extracellular matrix (ECM) components. We examined the role of ECM laminin α4 (Lama4) using FRC-Lama4 conditional KO Pdgfrb-Cre–/– × Lama4fl/fl mice. Single-cell RNA-sequencing (scRNA-Seq) data showed the promoter gene Pdgfrb was exclusively expressed in FRCs. Depleting FRC-Lama4 reduced Tregs and dendritic cells, decreased high endothelial venules, impaired the conduit system, and downregulated T cell survival factors in LNs. FRC-Lama4 depletion impaired the homing of lymphocytes to LNs in homeostasis and after allografting. Alloantigen-specific T cells proliferated, were activated to greater degrees in LNs lacking FRC-Lama4, and were more prone to differentiate into effector phenotypes relative to the Treg phenotype. In murine cardiac transplantation, tolerogenic immunosuppression was not effective in FRC-Lama4 recipients, which produced more alloantibodies than WT. After lung transplantation, FRC-Lama4–KO mice had more severe graft rejection with fewer Tregs in their LNs. Overall, FRC-Lama4 critically contributes to a tolerogenic LN niche by supporting T cell migration, constraining T cell activation and proliferation, and promoting Treg differentiation. Hence, it serves as a therapeutic target for immunoengineering.